The COVID-19 crisis and counter-cyclical policies in Brazil - Luiz Fernando de Paula (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
This paper examines the Brazilian economy during the COVID-19 pandemic and the economic policies implemented in 2020 to address the economic and social crisis. Using primary and secondary sources, the article differs in its analysis from other heterodox approaches according to which state action in response to the pandemic crisis in Brazil was weak and inconsistent. It is argued that counter-cyclical actions, especially those relating to emergency aid, have had a strong counter-cyclical effect on the economy and on reducing poverty and social inequality, even though there was no strategy previously coordinated by the federal government. The article concludes that the poor outlook for the Brazilian economy relates to both the resumption of orthodox policies and the unleashing of a second wave of the COVID-19 pandemic, both contributing to a slow recovery of the Brazilian economy.
Keywords: B32; E61; E65; 330; Brazilian economy; COVID-19 crisis; Bolsonaro government